1997
DOI: 10.1136/jnnp.63.3.368
|View full text |Cite
|
Sign up to set email alerts
|

PET and SPECT in whiplash syndrome: a new approach to a forgotten brain?

Abstract: Whiplash associated disorders are a medicolegally controversial condition becoming increasingly worrisome in the western world. This study was designed to evaluate perfusion and glucose metabolism in whiplash brain. Using Tc-99m-bicisate (ECD) single photon emission computed tomography (SPECT) and F-18-fluorodeoxyglucose (FDG) PET, six clinically and neuropsychologically controlled patients (patient group) with whiplash syndrome and 12 normal controls (control group) were investigated. Standardised elliptical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 11 publications
5
31
2
Order By: Relevance
“…The finding of a reduced rCBF in the left temporoparietal region, mainly located in somatosensory area in the whiplash group compared to the healthy group (Fig. 1b) is interesting, even though not significant, since it is in concordance with previous studies showing changes in these regions [29]. This reduction might support afferent pain input with absent pain processing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The finding of a reduced rCBF in the left temporoparietal region, mainly located in somatosensory area in the whiplash group compared to the healthy group (Fig. 1b) is interesting, even though not significant, since it is in concordance with previous studies showing changes in these regions [29]. This reduction might support afferent pain input with absent pain processing.…”
Section: Discussionsupporting
confidence: 79%
“…Generalised hypersensitivity and central nervous pain mechanisms have been the focus of interest lately [2,9,38]. Earlier studies indicate a parieto-occipital hypoperfusion but it is unclear if the hypoperfusion represents a response to chronic pain [14,[28][29][30][31]. It has been suggested that these blood flow changes may be caused by activation of nociceptive afferent nerves from the cervical spine [29].…”
mentioning
confidence: 99%
“…On the other hand, the structure of the proteins is altered during hydrolysis since buried hydrophobic groups are exposed and free to interact. It is proposed that noncovalent interactions, mainly electrostatic and hydrophobic, are major interacting forces since they promote aggregation and subsequent gel settings (Fuke et al, 1985, Otte et al, 1996, Otte et al, 1997, Jeewanthi et al, 2015. However, Kuipers et al (2005) concluded based on their findings that the aggregation is not a simple balance between repulsive electrostatic and attractive hydrophobic interactions, but much more complex.…”
Section: Gelling Propertiesmentioning
confidence: 95%
“…There may be several explanations for these results, and one possibility that the authors discussed was central dysfunction among patients with the most pronounced changes. Studies using positron emission tomography (PET) and single-photon emission computed tomography (SPECT) in patients with long-term complaints after whiplash injury have found parieto-occipital hypoperfusion [188][189][190][191]. However, Bicik et al [16] found no correlation between abnormal PET or SPECT findings and either cognitive symptoms or metabolic changes, and concluded that such examinations were of no diagnostic value for the individual patient.…”
Section: Central Nervous Systemmentioning
confidence: 96%